2012
DOI: 10.1002/app.38522
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polyvinylidene fluoride (PVDF) membranes for protein binding: Effect of casting thickness

Abstract: Microporous polyvinylidene fluoride (PVDF) membranes were synthesized from PVDF/N-methyl-2-pyrrolidinone (NMP) solutions using an immersion-precipitation method with a 2-propanol/water mixture as a soft coagulant. The effects of membrane thickness on pore size distribution and surface/cross-section morphology were studied using capillary flow porometry and scanning electron microscopy (SEM), respectively. All the synthesized membranes had a small range of pore size distribution, with the pore size decreasing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 23 publications
(24 reference statements)
2
15
0
Order By: Relevance
“…Subsequently, a rapid phase separation takes place, and more porous membranes with larger pore sizes are created. From the kinetic point of view, many researchers indicated that increasing solution viscosity, as a result of the higher polymer concentration, prevents diffusion of nonsolvent through the cast film during the early part of phase separation, and this results in formation of smaller pores and fewer cavities.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, a rapid phase separation takes place, and more porous membranes with larger pore sizes are created. From the kinetic point of view, many researchers indicated that increasing solution viscosity, as a result of the higher polymer concentration, prevents diffusion of nonsolvent through the cast film during the early part of phase separation, and this results in formation of smaller pores and fewer cavities.…”
Section: Resultsmentioning
confidence: 99%
“…The membrane fabrication technique employed in this study was phase inversion technique which has been discussed elsewhere in details [8]. A pre-determined amount of PES and additive (MnO 2 and PVP) were weighed and added to NMP solvent.…”
Section: Membrane Preparationmentioning
confidence: 99%
“…Symmetrical, microporous PVDF membranes were prepared via non solvent-induced phase inversion according to a previously published method, with polymer concentrations of 13.0, 16.0, and 19 wt% (designated M1, M2 and M3 respectively) 15 . The casting process was performed at room temperature using an automatic fi lm applicator (Elcometer 4340 Motorised, Elcometer, UK) with an initial casting thickness of 500 μm and a casting speed of 30 mm/s.…”
Section: Membrane Preparationmentioning
confidence: 99%